IMPLEMENTASI PENDIDIKAN KESIAPSIAGAAN BENCANA BERBASIS PENDEKATAN KOGNITIF DI SEKOLAH DASAR NEGERI 1 DOYONG, KECAMATAN MIRI, KABUPATEN SRAGEN - Setyorini, Safitri; Purwanto, Danang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low level of disaster preparedness among elementary school students, particularly in dealing with floods, is caused by the absence of structured disaster education tailored to the characteristic of students. This study aims to describe the implementation of the Disaster Preparedness Education program in improving student preparedness at SD Negeri 1 Doyong. This research employed a qualitative descriptive approach, with data collection techniques including observation, interviews, and documentation. The results of the study show that the use of a gradual learning strategy-consisting of disaster socialization and disaster simulation aligns with the concrete operational stage of Jean Piaget’s cognitive theory and is effective in enhancing student’s cognitive understanding of flood preparedness steps. The implementation of the program applied an interactive approach, which increased student enthusiasm. However, several obstacles were encountered that affected the program;s overall effectiveness. Therefore, further actions are needed to strengthen disaster education, such as periodic training.